2019
DOI: 10.1007/s40980-019-00056-0
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Case of Minneapolis–St. Paul, MN: Locational Attainments and Segregation in the Twin Cities

Abstract: The Minneapolis-St. Paul Metropolitan Area has a rapidly growing foreign-born population in part due to its high levels of refugee reception and migrants drawn to the burgeoning high-tech and manufacturing industries. As a result, the Twin Cities are unique in that every major racial group has a sizable foreign-born segment with a wide range of U.S. entry experiences and thus the area offers an opportunity to investigate the dynamics of locational attainments and segregation of a highly diverse non-White popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
2
5
2
Order By: Relevance
“…In general, group differences in resources are less important to White-Black segregation, as Black locational attainments more strongly reflect place stratification effects. We also find that the classical spatial assimilation model is less applicable to understanding Black segregation as nativity works in the opposite direction for Black households in comparison with Latino and Asian households, consistent with our past research and suggesting a pattern of segmented assimilation (Crowell and Fossett 2020). While a deeper analysis of Black immigrant segregation is beyond the scope of this study, other research has offered further insight into variation in Black immigrant segregation patterns (Scopilliti and Iceland 2008;Tesfai 2019).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In general, group differences in resources are less important to White-Black segregation, as Black locational attainments more strongly reflect place stratification effects. We also find that the classical spatial assimilation model is less applicable to understanding Black segregation as nativity works in the opposite direction for Black households in comparison with Latino and Asian households, consistent with our past research and suggesting a pattern of segmented assimilation (Crowell and Fossett 2020). While a deeper analysis of Black immigrant segregation is beyond the scope of this study, other research has offered further insight into variation in Black immigrant segregation patterns (Scopilliti and Iceland 2008;Tesfai 2019).…”
Section: Discussionsupporting
confidence: 88%
“…The implications of this framework for understanding the segregation patterns of the groups considered here is that we may not observe uniform patterns of locational attainments but may in fact find attainment patterns that run counter to what the spatial assimilation hypothesis would have us expect (South, Crowder, and Chavez 2005b). For example, in our past research on the Minneapolis-St. Paul metropolitan statistical area, we found that US-born Black households were more likely to be segregated from White households than foreign-born Black households, counter to what we found for Latino and Asian households (Crowell and Fossett 2020). From the segmented assimilation perspective, we argue this pattern results because Black households experience a trajectory of assimilation that is more strongly impacted by institutionalized racism and particularly an established legacy of Black residential segregation.…”
Section: Segmented Assimilationcontrasting
confidence: 96%
See 3 more Smart Citations